2019
DOI: 10.1039/c9qi00233b
|View full text |Cite
|
Sign up to set email alerts
|

Two CuxIy-based copper–organic frameworks with multiple secondary building units (SBUs): structure, gas adsorption and impressive ability of I2 sorption and release

Abstract: Two CuxIy-based copper–organic frameworks with multiple SBUs have been successfully synthesized. Both the compounds exhibit high performance for I2 sorption and release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Thus, CPs have attracted increasing attention in the recent years. [25][26][27][28][29][30][31] It was found that the adsorption of I 2 by crystalline porous materials, including CPs, was based on noncovalent interactions like halogen bonding interactions between I 2 and Lewis basic sites [32][33][34][35] or charge-transfer interactions between the electron-poor I 2 and π-electron rich aromatics. [36][37][38][39][40][41] Thus, a combination of halogen bond and CT interactions between the guest I 2 molecules and the host frameworks imparts a comprehensive tuning effect on the iodine capture process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CPs have attracted increasing attention in the recent years. [25][26][27][28][29][30][31] It was found that the adsorption of I 2 by crystalline porous materials, including CPs, was based on noncovalent interactions like halogen bonding interactions between I 2 and Lewis basic sites [32][33][34][35] or charge-transfer interactions between the electron-poor I 2 and π-electron rich aromatics. [36][37][38][39][40][41] Thus, a combination of halogen bond and CT interactions between the guest I 2 molecules and the host frameworks imparts a comprehensive tuning effect on the iodine capture process.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Copper(I) iodide-based compounds with organic ligands have drawn the attention of researchers due to their rich luminescence properties with potential technological applications in OLEDs, 30 sensors, 31 and adsorption processes. 32,33 To date, the motifs of various structural conformations of Cu(I) iodide have been reported, for example, the Cu 2 I 2 rhomboid dimer, Cu 4 I 4 cubane or staircase tetramer, and Cu 6 I 6 eared cubane or staircase hexamer. 22,23 Besides, by following the principles of reticular chemistry, Cu x I y can be used as a secondary building unit bridged with organic ligands to construct diverse coordination networks.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Besides, by following the principles of reticular chemistry, Cu x I y can be used as a secondary building unit bridged with organic ligands to construct diverse coordination networks. 33,34 Copper(I) iodide-based compounds can also display multistimuli-responsive properties, which make them appeal to access original multifunctional materials. The most popular copper iodide cluster is the cubane compound formulated as [Cu 4 I 4 L 4 ] (L: organic ligand), which exhibits both mechanochromic and thermochromic luminescence properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine is one of the essential trace elements in human body, which can promote human growth and maintain the normal structure of the central nervous system. [14,15] However, the volatile radioactive iodine produced by nuclear fission (i.e., iodine isotopes 129 I and 131 I, with half-lives of 10 7 years and 8.02 days, respectively) is a highly mobile gas, which is easily absorbed by the human body and concentrated in the thyroid gland, seriously threatening human life and health. [16][17][18][19] Physical, chemical, and biological techniques have been extensively studied to treat pollutants in the past few years.…”
Section: Introductionmentioning
confidence: 99%